Pull-in Instability Analysis of Nanoelectromechanical Rectangular Plates Including the Intermolecular, Hydrostatic, and Thermal Actuations Using an Analytical Solution Methodology. (March 2019) - Samadani, F.; Ansari, R.; Hosseini, K.; Zabihi, A.
Abstract: The current paper presents a thorough study on the pull-in instability of nanoelectromechanical rectangular plates under intermolecular, hydrostatic, and thermal actuations. Based on the Kirchhoff theory along with Eringenʼs nonlocal elasticity theory, a nonclassical model is developed. Using the Galerkin method (GM), the governing equation which is a nonlinear partial differential equation (NLPDE) of the fourth order is converted to a nonlinear ordinary differential equation (NLODE) in the time domain. Then, the reduced NLODE is solved analytically by means of the homotopy analysis method. At the end, the effects of model parameters as well as the nonlocal parameter on the deflection, nonlinear frequency, and dynamic pull-in voltage are explored .